2015
DOI: 10.1016/j.actbio.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the inverse piezoelectric effect of trabecular bone on a micrometer length scale using synchrotron radiation

Abstract: In our study we report on the piezoelectric effect in bone which was already discovered and explored on a macro scale in the 1950. Clinical approaches utilize successfully electro stimulation to enhance bone healing but the exact mechanisms taking place are still a matter of debate. We have measured the stress distribution with micron resolution in trabecular bone to determine the piezo electric induced stress. Our results show that the magnitude of the induced stress is big enough to be sensed by cells and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…One example is in long bones showing the accumulation of charges when exposed to mechanical stress or strain: On the concave side negative charges accumulate and bone formation can be observed, whereas positive charges and bone resorption occur on the convex side [13]. These effects are attributed to streaming potentials [14][15][16] and piezoelectricity [17][18][19]. Also, some studies hypothesize strong interdependencies between both phenomena [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…One example is in long bones showing the accumulation of charges when exposed to mechanical stress or strain: On the concave side negative charges accumulate and bone formation can be observed, whereas positive charges and bone resorption occur on the convex side [13]. These effects are attributed to streaming potentials [14][15][16] and piezoelectricity [17][18][19]. Also, some studies hypothesize strong interdependencies between both phenomena [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As inspired by the piezoelectric property of bones, Yu et al designed the microscale piezoelectric zones (MPZs) with the use of K 0.5 Na 0.5 NbO 3 ceramics to guide the stem cell osteogenic differentiation in vitro and in vivo 4. Indeed, when an inverse piezoelectric effect was introduced to bone, the strain induced in bone matrix could stimulate the cellular activity of bone cells and then improved bone regeneration 5. When low‐intensity pulsed ultrasound (LIPUS) was applied to porous titanium alloy scaffold, the micromechanical strain induced by LIPUS would therefore initiate osteoblastic differentiation, bone formation and maturation as well as bony ingrowth in the porous scaffold 6.…”
Section: Introductionmentioning
confidence: 99%
“…Aschero et al investigated the converse piezoelectric effect of bone through measuring its bulk change induced by an electric field (Aschero et al, 1996). Wieland et al used X-ray micro-diffraction to study the inverse piezoelectric effect of bone and measured the shear strain induced in a femur by an electric field (Wieland et al, 2015). Itoh et al reported that charges induced by an external electric field can affect bone growth as well as osteoblast activity (Itoh et al, 2006), which indicated that electrical signals may play an important role in bone remodeling processes.…”
Section: Introductionmentioning
confidence: 99%